Can someone show this function is convex using the definition (without taking gradient)? $$F(x) = x^TAx + b^Tx + c$$

where $A$ is symmetric positive semi-definite.


By definition of convex, for any $x,y\in\mathbb R$, we have $$f(\frac{x+y}2)\leq\frac12(f(x)+f(y))$$ Thus it is sufficient to reduce and prove that $$\frac12(x+y)^TA(x+y)\leq x^TAx+y^TAy\\ x^TAy+y^TAx\leq x^TAx+y^TAy$$ Namely $$(x-y)^TA(x-y)\geq0$$ which is directly followed by positive semi-definite.

  • $\begingroup$ How would this proof change if A were positive definite and not semi-definite? $\endgroup$ – user2553807 Feb 10 '14 at 22:21
  • $\begingroup$ Nothing except the condition when equality holds. $\endgroup$ – Shuchang Feb 11 '14 at 6:52
  • $\begingroup$ how do you expand $(x+y)^TA(x+y)$ to the next formula? $\endgroup$ – Dzung Nguyen Jul 23 '14 at 23:07
  • $\begingroup$ @DzungNguyen According to associative law and distributive law. $(x+y)^TA(x+y)=(x+y)^TAx+(x+y)^TAy$, and similarly for the left $(x+y)^T$. $\endgroup$ – Shuchang Jul 24 '14 at 2:58
  • 2
    $\begingroup$ The first three inequalities should be inverse. $\endgroup$ – Khue Feb 13 '16 at 5:52

Just to leave the answer for the general case online for future reference. A function is convex if $f(\lambda x + (1-\lambda) y) \leq \lambda f(x) + (1-\lambda) f(y)$ for all $\lambda\in[0,\;1]$.

It suffices to show for a quadratic function $f(x) = x^TQx$. Therefore using the definition of a convex function:

\begin{align} (\lambda x + (1-\lambda) y)^TQ(\lambda x + (1-\lambda) y)\leq \lambda x^TQx + (1-\lambda)y^TQy \end{align} Equality holds for $\lambda = 0\;\text{or}\;1$. Therefore consider $\lambda\in(0,1)$. The left hand side simplifies to: \begin{align} \lambda^2x^TQx + (1-\lambda)^2y^TQy + \lambda(1-\lambda)x^TQy + \lambda(1-\lambda)y^TQx\leq \lambda x^TQx + (1-\lambda)y^TQy \end{align} Rearranging the terms and simplifying one obtains: \begin{align} & \lambda(1-\lambda)x^TQx + \lambda(1-\lambda)y^TQy - \lambda(1-\lambda)x^TQy -\lambda(1-\lambda)y^TQx\geq 0 \\ & \Rightarrow x^TQx + y^TQy -x^TQy-y^TQx \geq 0 \\ & \Rightarrow (x-y)^TQ(x-y) \geq 0 \end{align} which is true for positive semi-definite $Q\succeq 0$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.